A new species of the genus Philarius (Crustacea: Decapoda: Palaemonidae) from Ryukyu Islands, Japan - Mitsuhashi, Masako (Zootaxa, 2012)
A new species of scleractinian coral associating pontoniine shrimp, Philarius rufulus sp. nov. is described and illustrated based on a single ovigerous female from Ryukyu Islands.